Phaseolus vulgaris extract ameliorates high-fat diet-induced colonic barrier dysfunction and inflammation in mice by regulating peroxisome proliferator-activated receptor expression and butyrate levels - Avagliano, Carmen; De Caro, Carmen; Cuozzo, Mariarosaria; Liguori, Fabrizio Maria; La Rana, Giovanna; Micheli, Laura; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Paciello, Orlando; Russo, Roberto (Frontiers in Pharmacology, 2022)
Obesity is a health concern worldwide and its onset is multifactorial. In addition to metabolic syndrome, an high-fat diet induce many deleterious downstream effects such as chronic systemic inflammation, a loss of gut barrier integrity and gut microbial dysbiosis, with a reduction of many butyrate-producing bacteria. These conditions can be ameliorated increasing legumes in the daily diet. White and kidney beans (Phaseolus vulgaris L.) and its non-nutritive bioactive component phaseolamin was demonstrated to mitigate several pathological features related to a metabolic syndrome-like condition. The aim of the present study was to investigate the molecular pathways involved in the protective effects on intestinal and liver environment of a chronic oral treatment with P. vulgaris extract (PHAS) on a murine model of high-fat diet. Results show that PHAS treatment has an anti-inflammatory effect in liver, colon and cecum. This protective effect was mediated by peroxisome proliferator-activated receptor (PPAR)-α and γ. Moreover, we also observed that repeated PHAS treatment was able to restore tight junctions expression and protective factors of colon and cecum integrity disrupted in HFD mice. This improvement was correlated with a significant increase of butyrate levels in serum and fecal samples compared to HFD group. These data underline that a prolonged treatment with PHAS significantly reduces some pathological features related to metabolic syndrome-like condition, such as inflammation and intestinal barrier disruption; therefore, PHAS could be a valid tool to be associated with the therapeutic strategy.